Aspergillus fumigatus-Associated Disease Spectrum, Virulence Factors, Pathogenicity, and Currently Used Diagnostic Approaches - Priya Koundal; Sunita Manhas; Shakeel Ahmed Mohammed; Kajal; Ajaydeep Singh; Jay Punjani; Shahbaz Aman; Adesh K. Saini (Journal of Pure and Applied Microbiology)
Aspergillus fumigatus is a pathogenic fungus that causes fatal infectious human disease known as aspergillosis. Fungus A. fumigatus is capable of causing infections in various body parts of humans, but it primarily infects the lungs and causes pulmonary infections known as allergic bronchopulmonary aspergillosis (ABPA). Subsequent dissemination of A. fumigatus into the deeper body parts may also contribute to the development of invasive infections in other vital organs. Therefore, the complexity and spectrum of aspergillosis majorly include allergic and invasive infections. To dominate the human body and escape the human immune system, A. fumigatus produces a number of virulence factors as well as pathogenicity determinants to establish disease. These pathogenic moieties of A. fumigatus includes allergens, toxins, hydrophobins, integrins, mannans/galactomannans, lectins, adherins and many other proteins with unknown functions. Combinatorially, these components make A. fumigatus a successful pathogen for humans, although, additionally the A. fumigatus pathogenicity has also been influenced by the metabolism of nitrogen/amino acids, folate synthesis, metal ions, cell wall biosynthesis as well as protein degradation mechanisms. A number of tools and techniques are being used to provide an accurate and timely laboratory diagnosis of aspergillosis. Such comprehensive tools include microscopic examination, culture, and antigen detection methods, serological assays and molecular techniques (DNA probes and molecular typing), G-test and D-mannitol detection and others. However, identifying fungi and assessing antifungal susceptibility by detecting galactomannans and Aspergillus-DNA are also useful. However, certain limitations exist in determining the circulating biomarkers that can be addressed via upcoming approaches such as lateral flow devices and next-generation sequencing. According to current understandings, the biology and clinical impact of A. fumigatus have been complex; therefore, updated information about virulence mechanisms, clinical manifestations, and diagnosis intricacies is essentially required for effective and better management and treatment of Aspergillus-induced infections.